Combustion of Boron and Boron-Containing Reactive Composites in Laminar and Turbulent Air Flows. Issue 4 (3rd April 2017) - Wang, Song; Schoenitz, Mirko; Dreizin, Edward L.
ABSTRACT: Combustion of boron and reactive composite powders of Al·B·I2 and Mg·B·I2 in air is characterized experimentally. Composite materials are prepared by mechanical milling of elemental starting materials. Particle size distributions for each material and fractal dimensions of the particle agglomerates are characterized using electron microscopy. All powders are injected into a CO2 laser beam and ignited. A turbulent flow pattern is generated just above the laser beam using a cylindrical air knife. Combustion of individual particles is characterized optically in laminar and turbulent flows. Measured particle size distributions are correlated with the measured distributions of the burn times for each powder. Thus, particle burn times are obtained as a function of the particle size. For boron, the exponent of the power law describing the effect of particle size on its burn time is close to 1 for all flow conditions. Temperatures of the burning particles are also measured. It is observed that both boron particle burn times and temperatures are reduced markedly in turbulent flows. For laminar flow, two stages in the produced emission patterns are identified for burning boron particles. The first stage, accompanied by higher temperatures, is suppressed in the turbulent flow. Conversely, neither burn times nor temperatures are affected substantially by the flow conditions for both Al·B·I2 and Mg·B·I2 powders. For Al·B·I2 and Mg·B·I2 composite powders the exponents of the power law describing the effect of particle size on its burn time are close to 1.7 and 2, respectively. Combustion temperatures in air vary around 1800 K and 2300 K for Al·B·I2 and Mg·B·I2 powders, respectively.